1991
DOI: 10.1063/1.105516
|View full text |Cite
|
Sign up to set email alerts
|

New buffer layer for high-temperature superconducting ceramics on sapphire: LaBa2Cu3Oy/Ag bilayers

Abstract: We have grown highly oriented LaBazCu,Oy (1 lO)/Ag (111) bilayers on sapphire (1120). This structure constitutes a potentially excellent buffer layer for the growth of l-2-3 ceramic oxides on sapphire substrates. This bilayer does not show superconductivity in resistive measurements. A DyBa2Cu30,, film grown on this bilayer also exhibited (110) orientation. Sapphire (a-A1203) is a desirable substrate for the growth of superconducting thin films due to its low dielectric constant and the extensive interest on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The magnitude of voltage levels appearing in regular oscillations suggests that the physical case evolves in the intergranular region where the superconducting order parameter was suppressed by the addition of Ag and partly in the grains, since the grains have superconducting properties better than that of the weak link structure. As is well known, addition of Ag into the superconducting matrix improves the grain boundaries and also causes an increase in the normal state and superconducting properties of the corresponding material [10][11][12]. In a recent paper, we showed that the voltage oscillations in undoped YBCO take positive values with a background voltage value despite the fact that the driving current is bidirectional [4].…”
Section: Resultsmentioning
confidence: 95%
“…The magnitude of voltage levels appearing in regular oscillations suggests that the physical case evolves in the intergranular region where the superconducting order parameter was suppressed by the addition of Ag and partly in the grains, since the grains have superconducting properties better than that of the weak link structure. As is well known, addition of Ag into the superconducting matrix improves the grain boundaries and also causes an increase in the normal state and superconducting properties of the corresponding material [10][11][12]. In a recent paper, we showed that the voltage oscillations in undoped YBCO take positive values with a background voltage value despite the fact that the driving current is bidirectional [4].…”
Section: Resultsmentioning
confidence: 95%
“…1) and LaiBa2Cu307 (Ref. 2) have been used as a buffer layer and a protection layer for single thin films as well as multilayers3 on MgO or SrTiO3. Other superconductor/buffer layer pairs exist such as (La, Sr)2CuO4/Sm2CuO4 (Ref.…”
Section: Introductionmentioning
confidence: 99%